2021
DOI: 10.18343/jipi.26.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Perubahan Penggunaan Lahan dan Karakteristik Hidrologi DAS Citarum Hulu

Abstract: The Citarum watershed is one of the priority watersheds due to problems of critical land, flooding, erosion, and sedimentation which continue to increase every year. As the main catchment area that contributes to maintaining the availability of water resources, the upstream Citarum watershed continues to experience a reduction in forest and an increase in built-up land. A research aimed to analyze land use changes to the hydrological characteristics was carried out at the Watershed. The methods used include in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…The Very unhealthy level (on average) shows that there is no continuity of water flow and the ability of the land to infiltrate the water. This is due to the reduction of permanent vegetation land over several years based on [22]. According to [22], the upper Citarum watershed has decreased permanent vegetation by 11.5% within ten years (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Very unhealthy level (on average) shows that there is no continuity of water flow and the ability of the land to infiltrate the water. This is due to the reduction of permanent vegetation land over several years based on [22]. According to [22], the upper Citarum watershed has decreased permanent vegetation by 11.5% within ten years (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the annual flow coefficient value that has been obtained using the calculation above is classified into five categories, such as (table 3): The calculation results are classified into five classes, i.e., 0-20% is very unhealthy, 20-40% is unhealthy, 40-60% is moderately unhealthy, 60-80% is healthy, and 80-100% is very healthy [18] [21]. Land use data in this study uses data from research by [22], who analyzed SPOT 6 and 7 high-resolution image data for conditions in 2009 and 2018 in the upper Citarum watershed [22]. Land change in the upper citarum watershed between 2009 and 2018 there was a decrease in rice fields (-17.4%), forests (-5,5%), shrubs (-60,8%), and land use increases in dryland farming (13%), built-up areas (39,7%), plantation (6,4%), and bare land (95,5%) [22].…”
Section: River Regime Coefficient (Kra)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that LULC change (vegetated cover to built-up land) contributes significantly to the frequent flood occurrences in the upstream Citarum Watershed (e.g. FRosyidie, 2013;Fernandos et al, 2020;Tanika et al, 2020;Yulianto et al, 2020;Atharinafi and Wijaya, 2021;Fadhil et al, 2021;Husodo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the built-up land in the upstream Citarum Watershed has decreased significantly. Fadhil et al (2021) found that during 2009-2018 the built-up land in the upstream Citarum Watershed increased 11,305 ha or 39.7% while the forest cover reduced by around 1,611 ha (5.5%). Husodo et al (2021) reported that the vegetated cover land in the upstream Citarum Watershed decreased around 35% within 1989-2019.…”
Section: Introductionmentioning
confidence: 99%